A Review of Environmental Noise Pollution and Impacts on Human Health in Rajshahi City, Bangladesh - Sarker, Pramath Chandra; Siddique, Md. Nur-E-Alam; Sultana, Sabina (Indonesian Journal of Environmental Management and Sustainability, 2023)
Noise pollution refers to excessive, unwanted, or disruptive sound in the environment. It can originate from various sources, such as road traffic, air traffic, railways, construction, using loudspeakers, industrial operations, and even household appliances. The purpose of the study was to review noise pollution and its effects on human health in Rajshahi City, Bangladesh. Most of the studies identified that the main source of noise pollution in the city is road traffic noise. The city is at a crossroads with prominent national as well as educational institutions like Rajshahi University, Rajshahi College, Varendra Museum, Bank of Padma River, Rajshahi University of Engineering and Technology, Hospital and Diagnostic Centre, BSCIC Industry, and numerous other educational institutions. All studies showed that noise pollution levels higher than the recommended acceptable limits were detected in various areas. Exposure to high levels of noise causes stress on human health, such as auditory, hearing, and nervous system damage, reducing productivity, insomnia, sexual impotency, respiratory, cardio-vascular, neurological, and outing damages, and limiting human life. It is recommended that affected sites develop a practical management approach for reducing noise pollution.